A Clash between Citizenship Projects at Utrecht’s Houtplein in the 1970s - Bongers, Jasper (TSEG - The Low Countries Journal of Social and Economic History, 2023)
This article explores the clashing of two citizenship projects at Utrecht’s Houtplein, a re-education facility for so-called asocial families. On the one hand, there was a citizenship project led by the Public Housing Association, which existed between 1924 and 1974. This organisation’s view was that inhabitants of the Houtplein could be developed into full members of the community if they learned to adhere to the norms of neatness and orderliness. On the other hand, there was the Action Committee Pijlsweerd, a left-leaning organisation consisting of students and other inhabitants of the Pijlsweerd neighbourhood, which challenged the Public Housing Association’s project in the 1970s. Although their goals were very different, also the Action Committee pursued a citizenship project. Their aim was to encourage the inhabitants of the Houtplein to claim citizenship in a direct manner, by standing up against the Housing Association’s alleged paternalism. Analysing the interactions, and ultimate clash, between these two projects provides insight into how citizenship was contested, at the Houtplein and beyond.